2018
DOI: 10.1016/j.tre.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Parallel importation in a supply Chain: The impact of gray market structure

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…It can be concluded that the customer has an important role. It is supported by Li et al (2018) and Acosta et al (2019), explained the mechanism how market structure and the behavior of agents are affecting price transmission.…”
Section: Introductionmentioning
confidence: 98%
“…It can be concluded that the customer has an important role. It is supported by Li et al (2018) and Acosta et al (2019), explained the mechanism how market structure and the behavior of agents are affecting price transmission.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, the profitability of gray markets largely depends on manufacturers' pricing decisions. Furthermore, the latest available studies [16,42,43] on multinational supply chains deterring PI neglect to capture the transaction costs involved in parallel import activities, which are essential for third-party arbitrage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, we assume that only the MNM's products are the parallel importer's target [43], while the LM's seldom suffers. MNM' products are more familiar to markets because of their better reputation and quality.…”
mentioning
confidence: 99%
“…In this section, we model the game and analyze the equilibrium outcomes under the four different scenarios (as described in Section 3.1) when the online and offline retailers conduct the Nash game, where firms choose quantities rather than prices, e.g., [3,17,24,27].…”
Section: Model Analysismentioning
confidence: 99%